2020
DOI: 10.1210/clinem/dgaa431
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy Per- and Polyfluoroalkyl Substance Concentrations and Postpartum Health in Project Viva: A Prospective Cohort

Abstract: Abstract Context Per- and polyfluoroalkyl substances (PFAS) are environmental chemicals linked to weight gain and type 2 diabetes. Objective We examined the extent to which PFAS plasma concentrations during pregnancy were associated with postpartum anthropometry a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 76 publications
(69 reference statements)
0
11
0
Order By: Relevance
“…Pregnancy is an understudied window of vulnerability for later-life maternal health [1,84], as the metabolic demands necessary for supporting fetal development may enhance maternal metabolic disease risk [2,3,85,86]. Recent epidemiological studies have shown an increased prevalence of life-long maternal metabolic alterations following gestational EDC exposures [23][24][25], yet few rodent models have explored the role of pregnancy per se by directly comparing non-pregnant and pregnant female mice, nor have they examined exposure to EDC mixtures, a phenomenon consistent with the human environment. The present pilot study examined the potential for protracted maternal metabolic toxicity following gestational EDC exposures, singly and in the mixture.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Pregnancy is an understudied window of vulnerability for later-life maternal health [1,84], as the metabolic demands necessary for supporting fetal development may enhance maternal metabolic disease risk [2,3,85,86]. Recent epidemiological studies have shown an increased prevalence of life-long maternal metabolic alterations following gestational EDC exposures [23][24][25], yet few rodent models have explored the role of pregnancy per se by directly comparing non-pregnant and pregnant female mice, nor have they examined exposure to EDC mixtures, a phenomenon consistent with the human environment. The present pilot study examined the potential for protracted maternal metabolic toxicity following gestational EDC exposures, singly and in the mixture.…”
Section: Discussionmentioning
confidence: 99%
“…TCDD was found to upregulate genes in inflammatory pathways in adipose tissue both in vitro and in vivo [102], and numerous other EDCs have been observed to alter the differentiation of adipocytes and expression of adipokines [24,[101][102][103]. Furthermore, in epidemiological studies, exposures during pregnancy to phthalates and per and polyfluoroalkyl substances, such as PFOA, have been associated with elevated long-term maternal weight gain, despite weight gain in pregnancy [23,24]. While such findings are notable, it is possible that a much greater risk is conferred given that women are exposed to multiple EDCs during pregnancy, and the effect of such mixtures on long-term maternal adiposity remains to be investigated [6][7][8][9]31].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Arsenic (As), Mercury (Hg), Lead (Pb), Copper (Cu), and other heavy metals are found either as contaminants or as natural components in the environment (Huang et al, 2011;Marshall et al, 2007). It is also known that environmental contamination with per-and polyfluoroakyl substances (PFAS) generated in industrial activity is a reality (Al Amin et al, 2020;Birru et al, 2021;Mitro et al, 2020;Xu et al, 2020). Exposure to these environmental factors has been shown to lead to health complications in adults, in which pregnant women are a high-risk group (Gómez-Roig et al, 2021;Liu et al, 2021;Rolland et al, 2020;Soomro et al, 2019).…”
Section: Heavy Metals and Pfas As Ecto-exposomementioning
confidence: 99%
“…In this respect, there is a growing interest in assessing chemicals that can interfere with hormonal function -a specific class of substances known as endocrine disruptors (EDs) -and their impact on human health (16). Accumulating evidence suggests that PFAS can also act as endocrine disrupting molecules, exerting proestrogenic (17) or anti-androgenic effects (18), as well as antagonistic activities at the level of thyroid hormone signalling both in vitro an in vivo (18,19), thus raising additional concerns, especially for the most vulnerable categories such as pregnant women, children, newborns and the elderly (20)(21)(22)(23)(24). In light of this problematic aspect, in this review we aim to summarize the current knowledge on PFAS as endocrinedisrupting agents in humans, focusing on legacy substances as well as short-chain substitutes.…”
Section: Introductionmentioning
confidence: 99%